The Aristotelian Rhetorical Theory: A Framework for Analyzing Pakistani Beauty Products Advertising (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
Advertising is one of the most basic forms of communication through media. Persuasion is one of the primary purposes of advertising. Customers are persuaded to buy products by advertising using different persuasive techniques. Both men and women increasingly rely on beauty products to look beautiful and have attractive spouses. Advertisements use rhetorical devices to persuade their viewers. Advertisements use language to achieve the purpose of persuasion. This paper analyzes advertising language considering Aristotle’s rhetorical theory. The three primary persuasive means are logos (logical appeal), pathos (emotional appeal), and ethos (ethical appeal). We examined these three methods in this paper in terms of how they are used to persuade consumers, and how they are perceived by them. In order to determine how Pakistani media utilizes Aristotle’s three means of persuasion in television advertisements, researchers studied beauty advertisementsin Pakistani media forthree months. There is a great deal of emphasis placed on persuasion in Pakistani advertising. Although Aristotle’s rhetoric theory was presented over 2000 years ago, it has proven to be highly effective in persuasion today.